Case Report: Celiac plexus block improves gastrointestinal Long COVID symptoms - Liu, Luke D.; Duricka, Deborah L. (Frontiers in Neuroscience, 2025)
Lingering symptoms following SARS-CoV-2 infection, recognized as the clinical entity “Long COVID,” are common. Gastrointestinal dysfunction during and after COVID have received little attention to date and remain largely unaddressed. We have previously shown that numerous symptoms of Long COVID excluding gastrointestinal symptoms improve or resolve following stellate ganglion blocks (SGB). Here, we are first to report successful treatment of persistent post-COVID epigastric pain and diarrhea in three patients using celiac plexus block, a procedure commonly used for visceral abdominal pain and implicating the autonomic nervous system in Long COVID-associated GI symptoms.